Revolutionizing Anti-Allergy Medications: A Comprehensive Review of Target Discovery and Medicinal Chemistry - Neha Sahu; Rizwan Arif (International Journal of Advance in Molecular Engineering, 2024)
Above the past few decades, the prevalence of allergy illnesses has been steadily rising, impacting 20–30% of the world's population. Multiple targets are involved in allergic reactions to infections of the skin, digestive tract, and respiratory system. Developing medications with a good curative efficacy and minimal side effects while utilizing novel multi-targets and processes in accordance with the clinical features of various allergic populations and allergens is the primary challenge facing research on anti-allergy therapies. The knowledge on possible therapeutic targets and the medicinal chemistry of synthetic anti-allergy small molecules are the main topics of this review. With reference to leukotriene production, wascium channel blockers, inhibitors of Th2 cytokines, histamine-1/4 receptor antagonists, and leukotrienes, the structure-activity relationship and the mechanism of compound-target interaction were highlighted. The investigation of chemical scaffold optimization and modification for various lead compounds, which is compiled in this review, should serve as a valuable resource for the drug design of related and promising research, such as allergy, in addition to improving the success rate and effectiveness of virtual screening for antiallergic drugs.
Keywords: Allergic reactions; Medications; anti-allergy therapies; antiallergic drugs; medicinal chemistry; synthetic anti-allergy small molecules